БНХАУ-ын баруун хойд бүс нутгийг эрчимтэй хөгжүүлэх бодлого ба ӨМӨЗО-ы мал аж ахуйн бүс нутгийн хөгжлийн төлөв - Н, Ариунгуа (Journal of International Studies, 2002)
English title: Policy for Intensive Development of North Western Region of China and Development Perspective of Animal Husbandry Region of Inner Mongolia Development Perspective Inner Mongolian Animals Region